2019
DOI: 10.3390/ijerph16224340
|View full text |Cite
|
Sign up to set email alerts
|

Can FinTech Development Curb Agricultural Nonpoint Source Pollution?

Abstract: The green development of FinTech empowerment has become a compelling theme in economic development. In this study, based on the weighted least squares (WLS) and threshold regression methods of cross-sectional data, we empirically examine the impact of FinTech development on agricultural nonpoint source (NPS) pollution, a major cause of impaired surface water quality. Our results show that there is an inverted “U” shape relationship between the development of FinTech and agricultural NPS pollution. That is, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…So far, over 56 million "ant trees" have been planted across the country with promising results. For example, the Saihanba Plateau in China, once a dusty wasteland, has become the world's largest manmade forest [51]. Generally speaking, the mechanism between agricultural economic growth and NPS pollution will be significantly different due to varying levels of financial development.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, over 56 million "ant trees" have been planted across the country with promising results. For example, the Saihanba Plateau in China, once a dusty wasteland, has become the world's largest manmade forest [51]. Generally speaking, the mechanism between agricultural economic growth and NPS pollution will be significantly different due to varying levels of financial development.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Generally speaking, the governance of agricultural NPS pollution is closely related to the economic growth rate and the economic development level. At different levels of economic development, a government's emphasis on environmental issues and interventions can also differ [51]. From the perspective of evaluation, agricultural economic growth is not only reflected in the expansion of agricultural production scale, but also the increase in agricultural economic benefits.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…However, under the intensive management pattern, China's agricultural production has increasingly relied on chemical fertilizers, 2 of 19 pesticides, plastic film and other modern means, and adopted the modern agricultural production mode characterized by high input, yield and waste [2,3]. These extensive production means and modes have resulted in greatly improved efficiency of agricultural production, while sacrificed agricultural ecological environment [4,5], such as polluted rural water and soil [6,7]. In agricultural production activities, dissolved or solid pollutants, such as soil particles, nitrogen, phosphorus, and pesticide heavy metals in farmland, would cause agricultural non-point source pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Labor market and fertilizer price policies affect the level of fertilizer application, which has an effect on agricultural NPS pollution emissions [19,20]. Jiang et al conducted research from a technical perspective, and believed that FinTech development can curb agricultural NPS pollution [21]. Schreinemachers and Tipraqsa studied the influence mechanism of agricultural land endowment on agricultural NPS pollution, and found that abundant agricultural land endowment helps to reduce the intensity of chemical fertilizer input, thus reducing NPS pollution [22].…”
Section: Literature Reviewmentioning
confidence: 99%